ATRIAL FIBRILLATION AND STROKE PREVENTION PRACTICES IN PATIENTS WITH CANDIDACY FOR ANTICOAGULATION THERAPY - Ullah, Ikram; Ahmad, Farooq; Ahmad, Salman; Hayat, Yasir (Journal of Ayub Medical College Abbottabad, 2015)
Background: Stroke secondary to Atrial Fibrillation is usually due to thrombi formed in the left atrium and left atrial appendage embolizing to cause ischemic stroke. Therefore, in patients with Atrial Fibrillation, antithrombotic therapy is recommended to prevent stroke. Vitamin K antagonist therapy is most widely used antithrombotic therapy for patients with valvular and non valvular AF. Aspirin is recommended only in low risk patients. This study was conducted to determine the stroke prevention practices in local patients with atrial fibrillation who were candidates for anticoagulation therapy. Methods: This was descriptive cross sectional study conducted at Cardiovascular Department Lady Reading Hospital Peshawar and Cardiology Department Hayatabad Medical Complex Peshawar. Sampling technique was non probability consecutive. Patients visiting OPD of respective hospitals with EKG evidence of AF and having CHADES VASC score 2 or more or having mitral stenosis and AF were included in the study. Patients with additional indications for anticoagulation were excluded from the study. Results: A total of 205 patients with atrial fibrillation were studied. Mean age was 60.7±14.7 years. Male were 55.6% (n=114) while 44.4% (n=91) were female. Of these 149 (72.7%) were candidates for anticoagulation based on CHA2DS2 VASc score of 2 and more or mitral stenosis with AF. Only 27.5% (n=41) patients were adequately treated with anticoagulant therapy using VKA or novel oral anticoagulant drugs. Majority of them were getting dual antiplatelet therapy (DAPT). Conclusion: Most patients with AF and high risk characteristics for thromboembolism are not receiving proper stroke prevention therapies.